Integral use of oil-based raw materials with “green solvents”: review and opportunities (Research, Society and Development, 2020)
Oilseeds are among the plants with the highest production in the world and are used for the manufacture of oils and fats for human consumption. In this process, co-products are generated, rich in phenolic compounds with proven health benefits, commonly intended for animal feeding. The extraction of these polyphenols is commonly done with organic, toxic, flammable and non-biodegradable solvents. Consequently, there is a greater appeal for the use of solvents and treatments that focus on “green” chemistry, avoiding environmental pollution and reducing the risks of accidents when handling toxic solvents. Due to these characteristics, deep eutectic solvents (DES), formed mainly of primary metabolites, such as organic acids, sugars, alcohols and amino acids associated with natural quaternary ammonium salts. DES have already been used to extract bioactive compounds from plants and beverages and more often used for the extraction of phenolic compounds and often achieving better results than common solvents. DES extracts are also associated with a greater stability, due to the hydrogen bonds between their components, responsible for even greater solubility and extraction of phenolic compounds. The aim of this review was not only to collect studies that used DES and its variants in the extraction of phenolic compounds from oilseeds raw materials, in addition to surveying the studies on the stability of these solvents under different storage conditions. The results available in the literature indicated the use of DES as promising, both in the extraction efficiency and in the stability of the extracted compounds.